May Measurement Month 2017: an analysis of the blood pressure screening campaign results in India—South Asia. (24th April 2019) - Jose, Arun Pulikkottil; Kondal, Dimple; Gupta, Priyanka; Maheshwari, Anuj; Kaushik, Aprajita; More, Arun; Patil, Mansi; Sharma, Meenakshi; Bhise, Mukund; Verma, Narsingh; Mishra, Rajesh; Ganorkar, Sachin; et al.
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative aimed at raising awareness of high BP and to act as a temporary solution to the lack of screening programmes worldwide. A recently conducted study on 1.3 million adults in India showed the prevalence of hypertension to be 25.3%. Raised BP is responsible for 8.5% of the total Disability Adjusted Life Years and is also an important contributor to cardiovascular disease which is the leading cause of deaths in the country. An opportunistic cross-sectional survey of volunteers aged ≥18 was carried out in May 2017. Blood pressure measurement, the definition of hypertension and statistical analysis followed the standard MMM protocol. The study was conducted in over 500 screening sites across the country and involved over 5000 volunteers. Screening sites included health facilities such as hospitals and clinics, as well as a variety of public spaces. A total of 240 376 individuals were screened during MMM17. Out of the 122 685 screenees for whom all three BP readings were available, 38 974 (31.8%) had hypertension based on the mean of second and third reading. Of individuals not receiving antihypertensive medication, 21 679 (17.7%) were hypertensive. Of individuals receiving antihypertensive medication, 14 203 (82.6%) had uncontrolled BP. MMM17 was the largest collaborative BP screening campaign undertaken in India with involvement of the public as well as the private sector. Over two-thirds of the individuals on antihypertensive treatment had uncontrolled BP. Approximately one-fifth of the participants had raised BP and were not on antihypertensive treatment prior to the study. These results suggest that opportunistic screening can identify significant numbers with raised BP.